2017
DOI: 10.1016/j.pedneo.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Neonatology oxidative status in preterm infants with premature preterm rupture of membranes and fetal inflammatuar response syndrome

Abstract: High pro-oxidant capacity was found in PPROM and low antioxidant capacity in PPROM and FIRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…According to Özalkaya et al TOS is much higher in cases of premature rupture of membranes and TAS is lower in cases of premature rupture of membranes and fetal inflammatory response syndrome. Also, they suggest that oxidative stress is responsible for the premature ageing of the fetal membranes of infants born before 34 weeks of gestation (57). This thesis is also supported by a number of studies carried out by Menon and Richardson (58) and Ilhan et al (59).…”
Section: Circulating Biomarkers and Oxidative Stress Evaluationmentioning
confidence: 64%
“…According to Özalkaya et al TOS is much higher in cases of premature rupture of membranes and TAS is lower in cases of premature rupture of membranes and fetal inflammatory response syndrome. Also, they suggest that oxidative stress is responsible for the premature ageing of the fetal membranes of infants born before 34 weeks of gestation (57). This thesis is also supported by a number of studies carried out by Menon and Richardson (58) and Ilhan et al (59).…”
Section: Circulating Biomarkers and Oxidative Stress Evaluationmentioning
confidence: 64%
“…The studies that reported a positive association between oxidative stress and/or development of diseases related to prematurity were 72.2% (n = 13); 27.7% (n = 5) showed no significant association. Positive correlations were found in IUGR; 8 , 13 , 25 NEC; 10 , 20 morbidity and mortality; 5 , 26 BPD, IVH; 10 FIRS; 21 early-onset neonatal sepsis; 22 RDS 12 and ROP. 27 CLD, 19 DNA damage, 4 IVH, 24 cardiac functions, 23 and endothelial dysfunction 9 were not associated with oxidative stress levels in included studies.…”
Section: Resultsmentioning
confidence: 92%
“…Synthesis of the articles, year of publication, type of study, sample, source of specimen, biomarkers, diseases evaluated, and the main outcomes are described in Table 1 . 3 , 4 , 5 , 8 , 9 , 10 , 12 , 13 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28
Figure 1 Flowchart of the study selection process for the integrative review on oxidative stress in premature newborns.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, higher level of oxidative stress and lower level of anti-oxidant capacity markers were observed in women with PPROM with consequent histological chorioamnionitis as compared with PPROM but without chorioamnionitis. Özalkaya et al demonstrated that umbilical cord pro-oxidant TOS level was higher in preterm infants without fetal inflammatory response syndrome (FIRS) and with PPROM compared to those without FIRS and PPROM (67).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%